If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -1 = 5x + -21 Reorder the terms: -1 + 10x = 5x + -21 Reorder the terms: -1 + 10x = -21 + 5x Solving -1 + 10x = -21 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -1 + 10x + -5x = -21 + 5x + -5x Combine like terms: 10x + -5x = 5x -1 + 5x = -21 + 5x + -5x Combine like terms: 5x + -5x = 0 -1 + 5x = -21 + 0 -1 + 5x = -21 Add '1' to each side of the equation. -1 + 1 + 5x = -21 + 1 Combine like terms: -1 + 1 = 0 0 + 5x = -21 + 1 5x = -21 + 1 Combine like terms: -21 + 1 = -20 5x = -20 Divide each side by '5'. x = -4 Simplifying x = -4
| 4ln(x)+3y^2-1=3ln(x)+2y^2+1 | | -5(6v-8)-2=-4(1-3v) | | 1.5x+(1-x)=1.126 | | Z=7(x-h) | | 6w=150 | | 7x+(-5y)+(-9x)+19y= | | 9u-18=3u+12 | | y=(s^2+31.5s+250)(0.0025s^2+0.05s+1) | | 4g=(4g)(x) | | 20*x+100*y=1000 | | 9x-4+18x-2=8x+10 | | Y=2y-5 | | 20.5k=82 | | 22-8=(-2)+v(-7) | | Y=-3sen(2x)/x^2 | | 8(x+2)+8x=2(8x+6) | | 8n=108 | | 3.8+x=0.6 | | -1(x+4)= | | 6.37+4.2c=7.4c+8.95 | | 8x+3=-53 | | -8a+(-15a)= | | 2x+8(9x+6)=48 | | (6x^2+7x-9)-(8x^2-4x+7)= | | (45x^2+36x^3)= | | 4x-2x+5=21 | | k/2-9=30 | | C=7000-4B | | 4-4x=-4(x-1) | | (2x)3=54 | | -7x^2-9x=0 | | 5(-6+a)= |